Implementation of Islamic Business Communication Management in Micro, Small and Medium Enterprises: Case Study of Roti Bakar Ahmad Pekanbaru - Saputra, Hendra Eka; Deswarta, Deswarta; Nasution, Hotman (PT. Riset Press International, 2025)
Mr. Ahmad's business, inspired by his uncle, specializes in selling baked bread products in various flavors. The target market includes the general community, students, and children. To promote his products, Mr. Ahmad utilizes banners, promotional coupons, word-of-mouth through friends and family, and social media platforms. In his customer interactions, he prioritizes excellent service by being friendly, polite, and maintaining high product quality. Additionally, he often offers promotional incentives, such as a free product after ten purchases, and provides ordering services via WhatsApp. However, a recurring issue arises as some customers fail to collect their orders despite reminders. A significant challenge faced by Mr. Ahmad is the unavailability of certain bread products ordered through WhatsApp, leading to customer dissatisfaction and a gradual shift to competing businesses. Mr. Ahmad acknowledges the critical role of technology in business communication and emphasizes the need for consistent practices to sustain his enterprise. Furthermore, he envisions support from institutions to provide training and coaching, enabling his business to adapt to modern trends. This aligns with research findings that highlight the Prophet Muhammad’s (SAW) approach to business, characterized by friendliness, politeness, consistency, and effective communication, which remain vital principles for successful entrepreneurship.